Role of bronchophonography in early diagnostics of bronchial asthma in children of preschool age - A. A. Pavlikov; Yu. L. Mizernitsky; V. I. Marushkov; I. M. Melnikova; L. B. Shubin (Бюллетень сибирской медицины, 2009)
The diagnostic significance of bronchophonography (BPG) for early detection of bronchial asthma (BA) in children from 2 to 5 years old is estimated. BPG was used to examine 210 children, including 110 children with often acute respiratory infections (ARIs), 35 children with the mild case of BA in the remission period, and 65 practically healthy children. In patients with BA compared to the group of practically healthy children, the indices of acoustic work of respiration in the high-frequency range (the so-called zone of obstructive changes) were increased, and this increase was reversible after pharmacological test with a bronchial spasmolytic. Similar changes of BPG were observed in 20% of patients with often ARIs, and two years later these children had typical clinical signs of BA. Indices of diagnostic sensitivity and specificity of BPG were equal to respectively 95.2 and 95.0%. Taking into account the relative simplicity and noninvasive character of BPG, this allows us to recommend the wide use of this method as a screening one for early diagnostics of BA in children of early and preschool age under hospital conditions.